Respiratory Syncytial Virus Pneumonia Treated with Lower-Dose Palivizumab in a Heart Transplant Recipient - J. L. Grodin; K. S. Wu; E. E. Kitchell; J. Le; J. D. Mishkin; M. H. Drazner; D. W. Markham (Case Reports in Cardiology)
Respiratory syncytial virus (RSV) is an important community-acquired pathogen that can cause significant morbidity and mortality in patients who have compromised pulmonary function, are elderly, or are immunosuppressed. This paper describes a 70-year-old man with a remote history of heart transplantation who presented with signs and symptoms of pneumonia. Chest computed tomography (CT) imaging demonstrated new patchy ground glass infiltrates throughout the upper and lower lobes of the left lung, and the RSV direct fluorescence antibody (DFA) was positive. The patient received aerosolized ribavirin, one dose of intravenous immunoglobulin, and one dose of palivizumab. After two months of followup, the patient had improved infiltrates on chest CT, improved pulmonary function testing, and no evidence of graft rejection or dysfunction. There are few data on RSV infections in heart transplant patients, but this case highlights the importance of considering this potentially serious infection and introduces a novel method of treatment.